2018
DOI: 10.1007/s12603-017-0899-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk proteins supplementation in older adults undergoing resistance training: A meta-analysis of randomized control trials

Abstract: Our findings provide evidence that supplementation of milk protein, in combination with resistance training, is effective to elicit fat-free mass gain in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 48 publications
7
58
2
Order By: Relevance
“…Results for the secondary endpoints, changes in performance between groups, modified intention-to-treat analysis* (Medians and interquartile ranges (Q1, Q3)) RT during admission and 12 weeks after discharge. However, both groups improved significantly for most parameters, and specifically the increase in LBM shows an adaptive response to the RT in agreement with the previous studies (11,(14)(15)(16)(17)(18)(19)(22)(23)(24) and established knowledge (45) . The placebo group generally improved more than the protein group, which is unexpected, as most systematic reviews and meta-analysis find additional effects of PrS (11,14,(17)(18)(19)23) , with only a few finding no effects (15,24) or conflicting results (16,21,22) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results for the secondary endpoints, changes in performance between groups, modified intention-to-treat analysis* (Medians and interquartile ranges (Q1, Q3)) RT during admission and 12 weeks after discharge. However, both groups improved significantly for most parameters, and specifically the increase in LBM shows an adaptive response to the RT in agreement with the previous studies (11,(14)(15)(16)(17)(18)(19)(22)(23)(24) and established knowledge (45) . The placebo group generally improved more than the protein group, which is unexpected, as most systematic reviews and meta-analysis find additional effects of PrS (11,14,(17)(18)(19)23) , with only a few finding no effects (15,24) or conflicting results (16,21,22) .…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that protein supplementation (PrS) alone can improve parameters of muscle strength, muscle mass and physical function in older adults (11)(12)(13) . Also, PrS has been shown to enhance the adaptive response to resistance training (RT) interventions (mostly 6-12 weeks' duration); however, not in all studies (11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) . A hypothesis is that those who are most weak, for example, frail and sarcopenic, or those having a low habitual protein intake might benefit more from a combined intervention of PrS and RT (11,(13)(14)(15)(16)19,22,(24)(25)(26) .…”
mentioning
confidence: 99%
“…Studies have noted that 30.3%–65.1% of older adults with knee or hip OA had a daily protein intake lower than the recommended daily allowance of 0.8 g/kg/day [ 26 , 27 ]. PS and protein-based diet interventions are believed to additionally increase the efficacy of ET in older adults [ 28 , 29 ]. However, inconsistent results have been obtained regarding the effectiveness of PS combined with ET (PS + ET), specifically in older adults with OA or in individuals who recently underwent total joint replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been suggested that older adults need higher total protein intake to counteract the attenuated post-prandial muscle protein turnover [11]. The benefits of protein supplementation for increased phosphorylation of mTOR [12,13] and on increasing muscle mass and physical performance have been extensively discussed in randomized clinical trials, systematic reviews and meta-analyses [14][15][16][17][18]. It is, however, unclear whether this can be extrapolated to diminishing muscle damage and, thus, whether improving the protein intake with supplements in vital older adults can result in a positive protein balance and increased muscle cell activity that likely stimulates myofibrillar accretion.…”
Section: Introductionmentioning
confidence: 99%